Bibliometric Analysis of Proactive Personality in Islamic Banking By Using VOSviewer Software - Muhammad Andi Prayogi (Journal of International Conference Proceedings, 2022)
This paper is part of a research paper that aims to analyze articles objectively using bibliometrics to uncover human resource management studies that focus on proactive personalities in banking in Indonesia while exploring future research trends. Scopus was selected as the database to identify comprehensive field studies. In total, 1500 articles were taken for bibliometric analysis. In order to facilitate bibliometric analysis, VosViewer software is used to visualize and analyze the information obtained. Research findings based on this paper have proven that research opportunities are still open in the future to conduct studies on proactive personality, while other researchers have not studied proactive personality in Islamic banking.Islamic banking.